Comprehensive evaluation of serum microRNAs as biomarkers in multiple sclerosis. Issue 5 (October 2016) - Regev, Keren; Paul, Anu; Healy, Brian; von Glenn, Felipe; Diaz-Cruz, Camilo; Gholipour, Taha; Mazzola, Maria Antonietta; Raheja, Radhika; Nejad, Parham; Glanz, Bonnie I.; Kivisakk, Pia; Chitnis, Tanuja; et al.
Abstract : Objective: To identify circulating microRNAs (miRNAs) linked to disease stage and disability in multiple sclerosis (MS). Methods: Sera from 296 participants including patients with MS, other neurologic diseases (Alzheimer disease and amyotrophic lateral sclerosis), and inflammatory diseases (rheumatoid arthritis and asthma) and healthy controls (HCs) were tested. miRNA profiles were determined using LNA (locked nucleic acid)-based quantitative PCR. Patients with MS were categorized according to disease stage and disability. In the discovery phase, 652 miRNAs were measured in sera from 26 patients with MS and 20 HCs. Following this, significant miRNAs ( p < 0.05) from the discovery set were validated using quantitative PCR in 58 patients with MS, 30 HCs, and in 74 samples from other disease controls (Alzheimer disease, amyotrophic lateral sclerosis, asthma, and rheumatoid arthritis). Results: We validated 7 miRNAs that differentiate patients with MS from HCs ( p < 0.05 in both the discovery and validation phase); miR-320a upregulation was the most significantly changing serum miRNA in patients with MS. We also identified 2 miRNAs linked to disease progression, with miR-27a-3p being the most significant. Ten miRNAs correlated with the Expanded Disability Status Scale of which miR.199a.5p had the strongest correlation with disability. Of the 15 unique miRNAs we identified in the different group comparisons, 12 have previously been reported to be associated with MS but not in serum. Conclusions: Our findings identify circulating serum miRNAs as potential biomarkers to diagnose and monitor disease status in MS. Classification of evidence: This study provides Class III evidence that circulating serum miRNAs can be used as biomarker for MS.